Persepsi Remaja Tentang Pendidikan Seksual Pranikah di SMAN 1 Kasimbar - Masauda, Cici Magfira Aj.; Bustamin; Rafiqah; Rauf, Abd; Bialangi, Mursito S.; Sabran, Moh. (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to describe adolescents’ perceptions of premarital sex education at SMA Negeri 1 Kasimbar. This research uses a descriptive quantitative research method. The population in this study consisted of 416 students. The sample in this study consisted of 104 students, selected using stratified random sampling from grades X, XI, and XII at SMA Negeri 1 Kasimbar. The research instruments used were observation, interviews, questionnaires, and documentation. The instrument test results were declared valid and reliable. The research results indicate that adolescents’ perceptions of premarital sexual education are, overall, in the very good category, with 89 students (85.6%) falling into the very good category, 14 students (13.5%) in the good category, and only 1 student (1.0%) in the sufficient category. The overall average score reached 3.53 on a four-point Likert scale. The aspect of parental role received the highest score with an average of 3.61, followed by attitudes at 3.58, information media at 3.55, school involvement at 3.48, and knowledge at 3.45. Thus, it can be concluded that adolescents are beginning to have a high awareness of the importance of correct and responsible understanding of sexuality. Therefore, sexual education needs to be integrated into Biology lessons at school to strengthen adolescents’ knowledge and positive attitudes towards reproductive health.